Prevalence of thyroid disorders in Malaysia - Shahar, Mohammad Arif (2017)
Our prevalence of thyroid dysfunction are compatible most studies world wide (2.1% for hypothyroidism and 3.4% hyperthyroidism). Prevalence of goitre is 9.3% and thyroid nodule is 3.6%. There may be pockets of iodine deficiency which contributes to goitre in rural areas. Goitre in the coastal areas are likely autoimmune. Large proportion of the population may be unaware that they have some sort of thyroid problems especially hypothyroidism and subclinical thyroid dysfunction